Use of Mother Tongue and Local Languages in Public Service Delivery in Nepal - Kafle, Bimala (Bhashalok भाषालोक, 2026)
The protection of linguistic diversity is a good strategy to promote unity in diversity in multilingual countries like Nepal. This includes adoption of multilingual policy, equal recognition to all languages, and official use of local languages in governmental works. Using customer’s mother-tongue and local languages in service delivery can make them feel more comfortable, respected and valued. This makes the governance more inclusive, accessible and participatory and therefore improving the quality of service delivery and achieving good governance. In this context, this article analyses the linguistic diversity in Nepal, policies and institutional mechanisms and international context related to the use of mother tongues and local languages in service delivery. Further, it highlights the efforts made so far including problems and challenges for preservation, promotion and development of languages, including the endangered local languages and minority languages.